Depression as an independent prognostic factor for all-cause mortality after a hospital admission for worsening heart failure. (1st October 2016) - Sokoreli, I.; de Vries, J.J.G.; Riistama, J.M.; Pauws, S.C.; Steyerberg, E.W.; Tesanovic, A.; Geleijnse, G.; Goode, K.M.; Crundall-Goode, A.; Kazmi, S.; Cleland, J.G.; Clark, A.L.
Abstract: Background: Depression is associated with increased mortality amongst patients with chronic heart failure (HF). Whether depression is an independent predictor of outcome in patients admitted for worsening of HF is unclear. Methods: OPERA-HF is an observational study enrolling patients hospitalized with worsening HF. Depression was assessed by the Hospital Anxiety and Depression Scale (HADS-D) questionnaire. Comorbidity was assessed by the Charlson Comorbidity Index (CCI). Kaplan–Meier and Cox regression analyses were used to estimate the association between depression and all-cause mortality. Results: Of 242 patients who completed the HADS-D questionnaire, 153, 54 and 35 patients had no (score 0–7), mild (score 8–10) or moderate-to-severe (score 11–21) depression, respectively. During follow-up, 35 patients died, with a median time follow-up of 360 days amongst survivors (interquartile range, IQR 217–574 days). In univariable analysis, moderate-to-severe depression was associated with an increased risk of death (HR: 4.9; 95% CI: 2.3 to 10.2; P < 0.001) compared to no depression. Moderate-to-severe depression also predicted all-cause mortality after controlling for age, CCI score, NYHA class IV, NT-proBNP and treatment with mineralocorticoid receptor antagonist, beta-blocker and diuretics (HR: 3.0; 95% CI: 1.3 to 7.0; P < 0.05). Conclusions: Depression is strongly associated with an adverse outcome in the year following discharge after an admission to hospital for worsening HF. The association is only partly explained by the severity of HF or comorbidity. Further research is required to demonstrate whether recognition and treatment of depression improves patient outcomes.